Evaluation of biological mechanisms of artemisinin on bovine mammary epithelial cells by integration of network pharmacology and TMT-based quantitative proteomics - Tong, Jinjin; Sun, Yang; Wang, Ziyue; Cui, Defeng; Jiang, Linshu (Frontiers in Pharmacology, 2022)
The sesquiterpene lactone, artemisinin, is a primary component of the medicinal plant Artemisia annua L., which has anti-inflammatory, antibacterial and antioxidant activities. However, the potential effects of artemisinin on the mammary gland of dairy cows and the underlying molecular mechanisms remain unclear. Here, we utilized systematic network pharmacology and proteomics to elucidate the mechanism by which artemisinin affects milk production and the proliferation of bovine mammary epithelial cells (BMECs). Nineteen bioactive compounds and 56 key targets were identified through database mining. To delineate the mechanism of Artemisia’s activity, a protein-protein interaction network and integrated visual display were generated from bioinformatics assays to explore the relationships and interactions among the bioactive molecules and their targets. The gene ontology (GO) terms and KEGG annotation suggested that the apoptotic process, cell division, p53 pathway, prolactin and PI3K-Akt pathways played vital roles in mammary gland development. Using proteomics analysis, we identified 122 up-regulated and 96 down-regulated differentially significant expressed proteins (DSEPs). The DSEPs had multiple biological functions associated with cell division, apoptosis, differentiation, and migration. GO enrichment analysis suggested that DSEPs may promote cell proliferation and regulate apoptosis in BMECs. KEGG pathway analysis indicated that several biological pathways, such as those involved in antigen processing and presentation, cell adhesion molecules and ribosomes, played significant roles in the effects of artemisinin on BMECs. These findings contribute to a comprehensive understanding of the mechanism by which artemisinin affects BMECs to improve mammary gland turnover by inducing cell proliferation and mammary gland development.